2018
DOI: 10.3390/molecules23040851
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bioactive Compounds from Calicotome villosa Stems

Abstract: A phenylethanoid, two steroids, a flavone glucoside and a chalcone have been isolated for the first time from the stems of Calicotome villosa together with a previously isolated flavone glucoside. Their structures were determined by spectroscopic analyses (NMR, HRMS) as basalethanoïd B (1), β-sitosterol and stigmasterol (2), chrysine-7-O-β-d-glucopyranoside (3), chrysine 7-((6′′-O-acetyl)-O-β-d-glucopyranoside) (4) and calythropsin (5). The crude extracts and the isolated compounds (except 4), were evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Similar results were also reported by Korkmaz et al (2020) for the antioxidant effect of C. latifolia [42] . Alhage et al (2018) reported that the radical scavenging ability of the aqueous extract of C. retrorsa was quite high (>90 %) [43] . Taşkın and Bitis (2016) tested the metal chelating abilities of various wild edible plants, including Campanula lyrata [44] .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were also reported by Korkmaz et al (2020) for the antioxidant effect of C. latifolia [42] . Alhage et al (2018) reported that the radical scavenging ability of the aqueous extract of C. retrorsa was quite high (>90 %) [43] . Taşkın and Bitis (2016) tested the metal chelating abilities of various wild edible plants, including Campanula lyrata [44] .…”
Section: Resultssupporting
confidence: 76%
“…[42] Alhage et al (2018) reported that the radical scavenging ability of the aqueous extract of C. retrorsa was quite high (> 90 %). [43] Taşkın and Bitis (2016) tested the metal chelating abilities of various wild edible plants, including Campanula lyrata. [44] In their study, the ethanol extract of C. lyrata was reported as one of the best extracts in the metal chelating assay.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…The method described by Alhage et al (2018) [ 41 ] was used with few modifications. Concentrations of samples (0.0001, 0.001, 0.01, 0.1, and 0.5 mg/mL) were prepared in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The plant has been used in traditional medicine by Mediterranean populations for the treatment of furuncle, cutaneous abscess, chilblain, and as an antitumor agent [ 20 – 22 ]. The bioactivities of CV plant extracts were ascribed to their content of flavone glucosides, alkaloids, and anthraquinones in the aerial parts [ 18 , 23 , 24 ] as well as flavonols and alkaloids in the seeds [ 25 ].…”
Section: Introductionmentioning
confidence: 99%